Relative Quality of Foreign Nurses in the United States - Patricia Cortés; Jessica Pan (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2012)
In recent years, the US has become increasingly reliant on foreign registered nurses to satisfy health care demands. The Philippines has emerged as the single largest source of nurses educated abroad, representing more than half of foreign nurses entering the US in the last decade. One of the main concerns raised by the importation of nurses is the quality of care that they provide. This paper addresses this question by analyzing the relative quality of foreign educated nurses and its evolution over time using Census data from 1980 to 2010 and wages as a measure of skill. We find a positive wage premium for nurses educated in the Philippines, but not for foreign nurses educated elsewhere. This premium cannot be explained by differences in demographics, education, work experience, location, or detailed job characteristics. The assimilation profile of Filipino nurses and the types of hospitals that hire them strongly suggest that the premium reflects quality differences and not just unobserved characteristics of the job that carry a higher wage but are unrelated to skill. We provide evidence that the wage premium is likely to be driven by strong positive selection into nursing among Filipinos resulting from the high and heterogeneous returns to the occupation generated by active government support for the migration of nurses in the Philippines.
Keywords: J61; J24; J44; 330; Nurses; Migration; Selection; Skills